Fostering a high-functioning team in cancer care using the 4R Oncology model: Assessment in a large health system. Issue 28 (1st October 2022) - Liu, Raymond; Weldon, Christine B.; Linehan, Elizabeth Shurell; Gordon, Nancy P.; Abbe, Thea; Hennings, Marti; James, Henie; Katzel, Jed Abraham; Ng, Chun Fai; Tomita, Megumi; Velotta, Jeffrey B.; Ossowski, Stephanie; et al.
Abstract : 57 Background: Delivering cancer care by high-functioning multidisciplinary teams promises to address care fragmentation and complexity, which threaten care quality, impact patient outcomes, and strain the oncology workforce. We assessed whether the 4R Oncology model (Trosman et al 2021) for team-based interdependent care delivery and patient self-management impacted team functioning at Kaiser Permanente Northern California (KPNC), a large community-based health system. Methods: We deployed the 4R intervention in breast and lung cancers at 4 KPNC centers. The intervention encompassed team development and care delivery optimizations enabling teamwork. 4R Care Sequences – novel patient-facing care plans outlining timing and sequence of care – informed team formation, activities and functioning. We assessed intervention along 4 characteristics of high-functioning teams (Vogel JOP 2016). Results: 4R facilitated development of a high-functioning team along all 4 characteristics. (1) We formed an internally and externally recognized multidisciplinary team of 24 specialties who assumed team responsibilities for relevant care. (2) All participants committed to a shared goal of delivering interdependent care at the optimal time and sequence based on Care Sequences. (3) The team conducted 40 optimizations to enable effective interdependent care: 22 in breast, 7 in lung, and 11 in both cancers (Table). The optimizations impacted 6 care domains at 4 points in care continuum. Half of optimizations entailed low effort; 70% resulted in improved process efficiency. (4) An ongoing teamwork adaptation process was established. Conclusions: 4R is an effective and feasible approach to fostering high-functioning teams, which may contribute to improvement of multidisciplinary care delivery and support viability of the oncology workforce. Our intervention and taxonomy of results inform other institutions motivated to strengthen teamwork and improve delivery of complex interdependent care.Taxonomy of interdependent care optimizations. Aspect Optimizations in breast cancer, n = 22, % Optimizations in lung cancer, n = 7, % Optimizations in both cancers, n = 11, % All optimizations, N = 40, % Care Domain Care related to surgery 32 14 - 20 Care related to systemic therapy 27 14 9 20 Genetics & biomarkers 14 29 - 13 Imaging, other assessment 9 29 - 10 Supportive care 5 14 73 25 Multi-Domain 14 -- 18 13 Point in care continuum Workup 41% 57 27 40 Preparation for treatment 27% 14 73 38 Transition between treatments 32% 29 - 23 Methods used in optimizations * Establish scheduling priority 14 71 36 30 Establish practice standards 59 71 100 73 Move up timing 77 86 82 80 Update or formalize workflow 68 71 82 73 Level of effort Low 55 43 45 50 Medium 27 14 9 20 High 18 43 45 30 Optimization produced efficiency in care delivery Yes 77 100 64 77 No 23 - 36 23 *Does not amount to 100%; multiple methods were used for some optimizations.